REPRESENTATION OF THE CONCEPT OF “RUSSIA” IN THE PRACTICE OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE - E.V. Tuktangulova (Многоязычие в образовательном пространстве)
Russian Russian is a foreign language concept. The article is devoted to the definition of some features of the representation of the concept of “Russia” in the Russian language picture of the world through educational complexes on Russian as a foreign language of the basic level (“The Road to Russia,” publishing house “Zlatoust”; “Journey to Russia,” publishing house “Russian language. Courses”), and the study of their influence on the formation of the image of Russia among foreign students. Currently, there is an urgent need to form a positive image of Russia and its representatives, which contributes to the development of interest in the language and culture of our country, the desire of foreign citizens to participate in intercultural events, and to get acquainted with the lifestyle of the Russian people. There are many ways to form a positive image of Russia, but the most important thing in the process of language learning, in our opinion, is the textbook of Russian as a foreign language. The purpose of the article is to analyse the texts and exercises in basic-level educational complexes through the prism of cultures.